Juridical and Fiscal Analysis of Carbon Tax as an Emission Control Instrument in the Indonesian Tax Financial System - imahda khori furqon; Minkhatun Nasikhah (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2025)
This study aims to analyze the juridical and fiscal aspects of the implementation of carbon tax as an instrument of emission control in Indonesia's taxation system. The carbon tax is regulated in Law No. 7 of 2021 on Harmonization of Tax Regulations (HPP Law), which marks a shift in the function of taxes from being a means of state revenue to an instrument of sustainable development. This research uses a normative juridical method with a qualitative approach to examine the legal basis, fiscal impact, and policy effectiveness on changes in business financial behavior. Although there have been many studies on the environmental and economic aspects of carbon tax, there are still few studies that comprehensively discuss the integration of juridical and fiscal aspects in the context of the national taxation system. The results show that carbon tax has strong constitutional legitimacy and is able to encourage corporate managerial transformation, but its implementation is faced with various challenges such as adaptation inequality between large companies and MSMEs, limited emission reporting, and immature technical regulations. Policy harmonization, capacity building, and fiscal incentives are needed for the carbon tax to be implemented fairly and effectively.